2006
DOI: 10.1143/jjap.45.774
|View full text |Cite
|
Sign up to set email alerts
|

Realization of High-Power Highly Efficient GaInP/AlGaInP Ridge Laser Diodes for Recordable/Rewritable Digital Versatile Discs

Abstract: Very efficient and reliable GaInP/AlGaInP red multiple-quantum-well laser diodes for recordable/rewritable digital versatile disc (DVD-R/RW) were successfully developed by low-damage fabrication. Because we adopted dry etching instead of conventional chemical wet etching for the steep ridge sidewalls of laser diodes (LDs), devices could be operated at a high output power over 200 mW at 70 C without showing any unstable higher-order transverse modes. In-situ monitoring tools in metal organic chemical vapor depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
(19 reference statements)
0
1
1
Order By: Relevance
“…Among these, D3 was attributed to Aluminum related defect, while D 1 and D 2 were not identified. On comparison, it is found that our emission rate data do not show any matching to those reported by Sugiura et al Byungjin et al [8] detected a defect related peak corresponding to energy 0.2 eV in their DLTS spectra of AlGaInP taken under two different ambient i.e. H 2 and N 2 .…”
Section: Resultscontrasting
confidence: 59%
“…Among these, D3 was attributed to Aluminum related defect, while D 1 and D 2 were not identified. On comparison, it is found that our emission rate data do not show any matching to those reported by Sugiura et al Byungjin et al [8] detected a defect related peak corresponding to energy 0.2 eV in their DLTS spectra of AlGaInP taken under two different ambient i.e. H 2 and N 2 .…”
Section: Resultscontrasting
confidence: 59%
“…Compared to devices with wavelengths X650 nm, where promising results have been achieved recently [1][2][3][4], the further reduced barrier heights for electrons and holes and the corresponding high leakage currents are a major challenge for the design of devices in the 63x-64x nm wavelength range [5][6][7]. These lasers operate at the physical limits and suffer from low efficiencies and a high temperature sensitivity.…”
Section: Introductionmentioning
confidence: 99%